2021
DOI: 10.1177/00333549211007152
|View full text |Cite
|
Sign up to set email alerts
|

SNAP Participants and High Levels of Food Insecurity in the Early Stages of the COVID-19 Pandemic

Abstract: Objectives The coronavirus disease 2019 (COVID-19) pandemic has disproportionately strained households experiencing poverty, particularly Black and Latino households. Food insecurity, which entails having limited or uncertain access to a sufficient quantity of nutritious food, is a key pandemic-related consequence. We examined how people enrolled in the Supplemental Nutrition Assistance Program (SNAP) have been affected by the pandemic, particularly Black participants and participants residing in food deserts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 14 publications
3
20
1
Order By: Relevance
“…(6,7) Studies focusing on the impact of COVID-19 on populations who were food insecure before the pandemic have mixed findings. Siddiqi, et al found that food insecurity increased significantly among participants enrolled in SNAP before and after the pandemic, (8) whereas Molitor et al reported that new federal benefits available in response to COVID-19 may have reduced very low food security among low-income households before and shortly after the economic downturn from the pandemic. (9) Feng, et al indicated that racial/ethnic disparities in food insecurity among African American and Hispanic/Latinx populations were exacerbated by the pandemic, (10) whereas Dubowitz, et al concluded that disparities had not worsened, but rather barriers differed among racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…(6,7) Studies focusing on the impact of COVID-19 on populations who were food insecure before the pandemic have mixed findings. Siddiqi, et al found that food insecurity increased significantly among participants enrolled in SNAP before and after the pandemic, (8) whereas Molitor et al reported that new federal benefits available in response to COVID-19 may have reduced very low food security among low-income households before and shortly after the economic downturn from the pandemic. (9) Feng, et al indicated that racial/ethnic disparities in food insecurity among African American and Hispanic/Latinx populations were exacerbated by the pandemic, (10) whereas Dubowitz, et al concluded that disparities had not worsened, but rather barriers differed among racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity, limited or uncertain access to sufficient, nutritious food for an active, healthy life, has increased in the United States (U.S.) during the COVID-19 pandemic due to severe economic disruption. ( Wolfson and Leung, Dec 2020 , The Impact of the Coronavirus on Food Insecurity in, 2020 ) Food insecurity continues to disproportionately impact lower-income households during the pandemic, ( Dubowitz et al, 2021 , Siddiqi et al, 2021 ) and is associated with numerous adverse short- and long-term outcomes including poorer mental health. ( Jones, Aug 2017 , Leung et al, Mar 2015 , Weinberger et al, Jun 2018 , Martin et al, Mar 2016 ) During the COVID-19 pandemic, existing race/ethnic and socio-economic-based health disparities have been exacerbated including those associated with food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps as a consequence of being largely unencumbered by the socioeconomic stresses identified as disproportionately affecting those in minoritized ethnic groups ( Barnes and Hamilton, 2020 ; Siddiqi et al, 2021 ), all interview participants described positively the ways in which pandemic lockdown had offered them opportunities for personal and/or social growth. This uninterrupted time enabled people to develop new or reinvigorate old hobbies and “take stock” of and “re-evaluate” their lives.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the United Kingdom, people in Black, Asian (and “other white”) groups reported poorer mental health and an increased sense of worry following the first pandemic lockdown 1 ( Barnes and Hamilton, 2020 ). Research from the US has also indicated higher risk of food scarcity as a consequence of the pandemic among marginalised ethnic groups which is likely to be replicated in the United Kingdom ( Siddiqi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%